(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
today in our country, foreign products or imports provide consumers with more choice. Because they are usually produced cheaper than the locally produced equivalent, imports help consumers manage their household budgets. In this article, Uzbekistan’s cooperation with foreign imports, implementation of import substitution projects in the Republic, the level of development of sectors in the economy, the availability of raw materials resources in the Republic, the constant demand of industries in production for imported goods, as well as for industries, the availability of necessary infrastructure and import substitutes.